The reality of the forms and goals of training and education program in the human management - Abang Mohd. Razif Abang Muis; Abdul Hair Beddu Asis (Pennwell Corporation, 2020)
This article aims to identify and analyse the form and goals of training and education programs in human management based on existing works. Issues of deterioration in workers' behaviour coupled with various misconduct such as corruption, trust and so on make aspects of the form and purpose of training and education programs in existing human resource management needs to be reviewed and re-evaluated. Among the questions that arise is what are the training and education programs in human management? What is the purpose of the training and education programs? The current scenario shows the various efforts of implementing training and education programs to improve the quality of workers in an institution. As such, this article attempts to examine this issue based on classical and contemporary secondary sources using qualitative content analysis and subsequently develops a mapping of the workings and goals of training and education programs in human management